Aspectos microbiológicos e epidemiológicos das infecções de corrente sanguínea pelo complexo Candida parapsilosis em hospitais da América Latina - Souza, Ana Carolina Remondi [UNIFESP] (2016)
The importance of C. parapsilosis species complex as agents of bloodstream infections has risen in recent years, however there is little data about the potential biological, epidemiological and clinical peculiarities related to these three species. In this study we evaluated the epidemiology, antifungal susceptibility profile and virulence of C. parapsilosis (sensu stricto), Candida metapsilosis and Candida orthopsilosis isolates recovered from bloodstream infections in different Latin America hospitals. A total of 317 isolates of C. parapsilosis (sensu lato) were tested and characterized in two groups: (i) Group 1 (308 isolates from hospitals in Latin America) and (ii) Group 2 (nine isolates from a private hospital in Brasilia, Brazil). Speciation of the isolates was confirmed through molecular identification using real time PCR. The in vitro antifungal susceptibility testing was performed using the CLSI broth microdilution methodology. Isolates of C. parapsilosis (sensu stricto) with minimum inhibitory concentration values (MIC) at or above the epidemiologic cutoff (ECV) to fluconazole were analyzed for molecular mechanisms of resistance to this drug. For virulence analysis, representative isolates of each species were analyzed for biofilm formation capability and pathogenesis using C. elegans model. For Group 1, among the 308 isolates, 274 (88,9%) were identified as C. parapsilosis (sensu stricto), 26 (8,5%) as C. orthopsilosis and eight (2,6%) as C. metapsilosis. All isolates were susceptible to amphotericin B and anidulafungin. Regarding fluconazole, 24 C. parapsilosis (sensu stricto) isolates exhibit MIC at or above the ECV, four of them were considered non-susceptible. According to the analysis for molecular mechanisms of drug resistance, 20 of them revealed that at least one mechanism is expressed in these isolates. All species of the complex C. parapsilosis showed equal ability to produce biofilms. Using C. elegans as an invertebrate model host, we observed that the three species of C. parapsilosis complex feature a similar pathogenic potential inducing different immune response of the infected host. For Group 2, all isolates were identified as C. parapsilosis (sensu stricto) and exhibited fluconazole resistance phenotype. About the expression of molecular mechanisms of resistance, all isolates showed a non-synonymous mutation in ERG11 and also overexpression of ERG11 and CDR1. The Galleria mellonella infection model was used to confirm in vitro resistance. Our results showed that bloodstream infections by C. parapsilosis species complex have clinical importance in Latin America, involving three species whose pathogenic potential seems very similar. Although infrequent, in vitro and in vivo fluconazole resistance can be documented in infections by C. parapsilosis (sensu stricto).